THE EFFECT OF ELECTRONIC MONEY USE AND LIFESTYLE ON THE CONSUMPTIVE BEHAVIOR OF ECONOMICS EDUCATION STUDENTS, INTAKE 2022-2024, HKBP NOMMENSEN UNIVERSITY, PEMATANGSIANTAR - May Afriyanti Sinaga; Benjamin Albert Simamora; Susy Alestriani Sibagariang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of electronic money use and lifestyle on the consumptive behavior of Economics Education Students, Intake 2022-2024, HKBP Nommensen University, Pematangsiantar. This study used a descriptive quantitative research method. Based on partial hypothesis testing, the results showed that electronic money had a positive and significant effect on consumptive behavior, as indicated by the calculated Tvalue (2.622) > Ttable (1.671), and lifestyle had no positive and significant effect on consumptive behavior, as indicated by the calculated Tvalue (1.265) < Ttable (1.671). Meanwhile, simultaneous hypothesis testing revealed that electronic money and lifestyle have a positive and significant effect on consumer behavior, as indicated by the calculated Fvalue (4.154) > Ftable (3.145). The coefficient of determination test yielded an R-square value of 0.120, indicating that 12% of the variables in electronic money and lifestyle influence the consumer behavior of Economics Education students in the 2022-2024 intake of HKBP Nommensen University, Pematangsiantar. The remaining 80% is attributed to other variables not examined in this study.